A gestão das condicionalidades do Programa Bolsa Família no âmbito da assistência social: uma análise crítica da sua dimensão político-ideológica - Carnelossi, Bruna (2013)
This paper intends to discuss the issue of management of conditionality of Bolsa Família (PBF), under the Social Assistance Policy, especially with regard to its political-ideological dimension, impacting the historical process of consolidation of social protection (safety) income, secured by the policy. The investigative path is anchored in methodological principles of historical materialism dialectic, that marks the relationship between the theoretical and conceptual mediation, interpretation of the data collected, and the observation of the technical and operational aspects of the work done by social workers in meeting the families receiving the program . Seeks to present the sociological dimension, legal and political issues around, from three chapters. In the first chapter rescues the historicity of the protective capacity of the state and contextualizes the contemporary dynamic of a size not contributory. In the second, it seeks to record the historic features and principles of the institutionalization of the Social Assistance Policy, distinguishing the various policy guidelines and ethical barriers that orbit and prospects for the process of recognition and legitimacy of your income security secured. In the third chapter, points up the political dimension and the ideological assumptions of management format conditioner GMP, their aftermaths in the field of institutional income security, anchored on the principles of Social Assistance. The study shows, particularly, that the management structure Guests GMP is based on a perspective punitive, disciplinary and moralizing, distorting the principles of social assistance benefits